Private Messaging Service using AES Encryption and Toxicity Detection - R, Shanmuga Priya; M, Tharunraj; Berg D, Rozen; Kannan M, Sanjay (2022 International Conference on Electronic Systems and Intelligent Computing (ICESIC), 2022)
With the advancement of digital technology in recent decades, the style of communication and use of digital accessories in our daily lives has changed dramatically. It is undeniable that the introduction of the mobile phone/smart phone has improved our standard of living and made life easier. A private messenger is an application that enables for encrypted communication. To provide safe data transmission between the sender and recipient, a protected private instant messenger is required. The messenger gives main emphasis on textual value by checking the text toxicity using a ML model in a novel way by not storing meta data of user atany juncture without compromising the quality of messaging service which is not present in main stream messaging application. The architecture of private messengers is presented in this work. The proposed architecture was created and tested on a private messaging application, and the findings show that it can increase data security for messenger applications.